PENINGKATAN KEMAMPUAN MENULIS TEKS FABEL DENGAN PEMBELAJARAN BERBASIS PORTOFOLIO PADA SISWA KELAS VIII SMP NEGERI 1 PONDOK KELAPA BENGKULU TENGAH - Santi Yuliani (Universitas Bengkulu, 2017)
The purposeof this studyto describecomprehensivelythe increase in the Ability to Write Text Fabel with Portfolio Based Learning to Students of Class VIII SMP Negeri 1 Pondok Kelapa Bengkulu Tengah. The method usedis classroom action research. Sources of dataobtained througheighth grade studentsworksheetF.Data collection techniques inthis study isthe testing techniquesandnontes(observation, journals, andinterviews). This research wasconducted in three cycles. First cycleconsistedof2 meetings, the second cycleconsistsoftwosessions, andthe third cyclecomprisesone meetings. The test resultsofthis study indicate thatan increased abilityto writetextfablein students. The average value ofthe classinthe first cycle of63.6(enough) with apassing rateof 27%, increased inthe second cyclewith an averageof 70(good) with apassing rateof56.7%. Then increasedagaininthe thirdcycle, which amounted to76(excellent) with apassing ratereached86.7%.Kata Kunci: WritingTextFabel, LearningPortfolio